2005
DOI: 10.1128/aem.71.8.4407-4413.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the psl Operon in Pseudomonas aeruginosa PAO1 Biofilms: PslA Performs an Essential Function in Biofilm Formation

Abstract: The psl gene cluster, comprising 15 cotranscribed genes from Pseudomonas aeruginosa, was recently identified as being involved in exopolysaccharide biosynthesis and biofilm formation. In this study, we investigated the regulation of the psl gene cluster and the function of the first gene in this cluster, the pslA gene. PslA shows strong similarities to UDP-glucose lipid carriers. An isogenic marker-free pslA deletion mutant of P. aeruginosa PAO1 deficient in attachment and biofilm formation was used for comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 38 publications
4
92
1
Order By: Relevance
“…Previous studies showed that biofilm initiation by nonmucoid P. aeruginosa strains with mutations in the psl genes was deficient, most likely due to the reduced ability of these mutants to interact with cell surfaces (12,20,29,32). The attachment assays in these studies were performed with a rich medium, and it was unclear if Psl contributed to cell-surface interactions when bacteria were grown under other conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that biofilm initiation by nonmucoid P. aeruginosa strains with mutations in the psl genes was deficient, most likely due to the reduced ability of these mutants to interact with cell surfaces (12,20,29,32). The attachment assays in these studies were performed with a rich medium, and it was unclear if Psl contributed to cell-surface interactions when bacteria were grown under other conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Overhage and colleagues recently mapped the psl operon promoter 41 bp upstream of the pslA start codon (32). Their data also suggested that psl expression was localized to the centers of microcolonies within biofilms (32). In addition, Kirisits et al showed that the expression of psl and pel was elevated in variants isolated from aging P. aeruginosa PAO1 biofilms (22).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…This is an area requiring future research. Overhage and Campisano et al demonstrated that pslA and pslD, which encode a putative UDP-glucose lipid carrier and exporter, respectively, are essential for biofilm formation in strain PAO1 [23,24]. They also demonstrated that while psl is constitutively expressed in planktonic cells, its expression is localized to the center of developing biofilm microcolonies [24].…”
Section: Pslmentioning
confidence: 98%